The spillover effect of CSR initiatives on consumer attitude and purchase intent: The role of customer-company identification with the moderating effect of awareness - Samra Chaudary; Muhammad Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The purpose of the study is to contribute in the literature of Corporate Social Responsibility (CSR) by analyzing how well the customers identifies themselves with the ethics and values of the company i.e. various CSR activities (Sponsorship, Cause-Related Marketing and Philanthropy) and its spillover effect on the purchase intentions. The findings of the study are based on 230 sample size by using Structural Equation Modeling (SEM) and cluster analysis. The results indicate that a high level of identification between the customer and company leads to better attitudes towards the product or service of an organization. The study also tries to uncover the impact of awareness in customers regarding the CSR campaigns and how this increased level of awareness leads to positive consumer behavior. The findings are usefulness for managers and they should try to communicate more with CSR activities especially through CRM as it showed the impact on identification. Nonetheless the study has geographical and sample size limitations thus cannot be generalized.
Keywords: 330; corporate social responsibility; cause-related marketing; philanthropy; customer-company identification; sponsorship